Isogeometric analysis-based phase-field modeling of brittle fracture in piezoelectric materials - Kiran Raj (Nanyang Technological University, 2024)
Piezoelectric materials find extensive applications as sensors, actuators, and transducers, however, most of the functional piezoelectric ceramics though possessing excellent electromechanical coupling characteristics are often limited by brittleness and low fracture toughness. On the other hand, piezoelectric composites offer improved characteristics but suffer from stress concentrations and interface cracks due to geometric imperfections, resulting in crack nucleation and propagation under complex loading conditions. Traditional analytical and experimental approaches fall short in unravelling the intricate fracture behaviour of piezoelectric materials, necessitating the development of accurate and robust numerical methods. Isogeometric analysis (IGA), with its precise geometry representation and high-order approximation capabilities, has emerged as a promising approach. Additionally, the phase-field method (PFM) approximates cracks as narrow damage bands, providing a computational tool for fracture analysis. Therefore, the primary objective of this Ph.D. research is to develop a comprehensive and robust isogeometric analysis-based framework to investigate the fracture behavior of piezoelectric materials using the phase-field modeling approach.